FSH Requirements for Follicle Growth During Controlled Ovarian Stimulation - Abbara, Ali; Patel, Aaran; Hunjan, Tia; Clarke, Sophie A.; Chia, Germaine; Eng, Pei Chia; Phylactou, Maria; Comninos, Alexander N.; Lavery, Stuart; Trew, Geoffrey H.; Salim, Rehan; Rai, Raj S.; et al. (Frontiers in Endocrinology, 2019)
Introduction: Ovarian follicle growth is a key step in the success of assisted reproductive treatment, but limited data exists to directly relate follicle growth to recombinant FSH (rFSH) dose. In this study, we aim to evaluate FSH requirements for follicular growth during controlled ovarian stimulation. Method: Single center retrospective cohort study of 1,034 IVF cycles conducted between January 2012–January 2016 at Hammersmith Hospital IVF unit, London, UK. Median follicle size after 5 days of stimulation with rFSH and the proportion of antral follicles recruited were analyzed in women treated with rFSH alone to induce follicular growth during IVF treatment. Results: Starting rFSH dose adjusted for body weight (iU/kg) predicted serum FSH level after 5 days of rFSH (r2 = 0.352, p < 0.0001), median follicle size after 5 days of rFSH, and the proportion of antral follicles recruited by the end of stimulation. Day 5 median follicle size predicted median follicle size on subsequent ultrasound scans (r2 = 0.58–0.62; p < 0.0001), and hence time to oocyte maturation trigger (r2 = 0.22, P < 0.0001). Insufficient rFSH starting dose that required >5% dose-increase was associated with increased variability in follicle size on the day of oocyte maturation trigger, and negatively impacted the number of mature oocytes retrieved. Conclusion: Weight-adjusted rFSH dose correlates with follicular growth during ovarian stimulation. Early recruitment of follicles using a sufficient dose of rFSH from the start of stimulation was associated with reduced variability in follicle size at time of oocyte maturation trigger and an increased number of mature oocytes retrieved.